Epidemiology and control of ticks with medical and veterinary importance in South America - Santiago Nava (Universidad de Antioquia, 2017)
An accurate knowledge on ecological aspects of ticks is essential to design and evaluate the control methods and to make epidemiological inferences about tick-borne diseases. From a sanitary and economic perspective, Rhipicephalus (Boophilus) microplus, Amblyomma sculptum, Amblyomma tonelliae (both species belonging to the A. cajennense complex) and Amblyomma triste are among the species with greater relevance in South America. Rhipicephalus (Boophilus) microplus is the principal tick species affecting cattle, while A. sculptum, A. tonelliae y A. triste have medical relevance because they are usual parasites of humans and have capacity to transmit pathogenic rickettsiae. In addition, A. sculptum, A. tonelliae and A. triste are frequent parasites of cattle. Bovines play an important role maintaining natural populations of these Amblyomma species in different areas of the Southern Cone of America. In this way, the knowledge of the annual fluctuations in the population abundance of the four ticks above-mentioned is an indispensable tool for designing effective schemes of treatment with acaricides in cattle, and to determine the periods of the year where there is an increased risk of transmission of tick-borne diseases. The current state of the knowledge about these topics will be presented during the presentation given in this congress.